Morphology enhancement of SiO2 aerogel films grown on Si substrate using dense SiO2 buffer layer - Sun, Xiang-Yu; Wu, Chuan-Gui; Luo, Wen-Bo; Shuai, Yao; Zhang, Wang-Li (Rare metals, 2023)
Porous SiO 2 film has been widely studied due to its extensive applications in many fields. This paper presents a newly produced porous SiO 2 film made by traditional sol–gel method. Bare Si and Si with SiO 2 buffer layer were used as substrate. The SiO 2 buffer layer was 500 nm in thickness and was grown by thermal oxidization. The structural properties of SiO 2 aerogel films spin-coated on both materials were observed by optical microscope (OM) and scanning electron microscope (SEM). Results reveal that the surface of SiO 2 aerogel films on bare Si is rough and discontinuous. While flat and smooth surface is observed on sample with SiO 2 buffer layer. This indicates that by inserting SiO 2 buffer layer, the structural property of SiO 2 aerogel film deposited on Si is improved.